Correlation of Size and Redness of Pterygium on Tear Film and Dry Eye Symptoms - Phrueksaudomchai, Pakornkit (Asian Medical Journal and Alternative Medicine, 2024)
Purpose: This study aimed to investigate the correlation of size and redness of pterygium to tear film and dry eye symptoms. Setting/Venue: Thammasat University Hospital, Thailand Materials and Methods: 976 patients joined a hospital-based, retrospective cross-sectional study in Thammasat University Hospital. Severity of pterygium was measured and collected by size and redness; Tear film was measured and collected by Tear meniscus height (TMH) and Tear break up time (TBUT); Dry eye syndrome was measured and collected by Ocular surface visual analogue scale (VAS), Ocular Surface Disease Index (OSDI), Oxford corneal staining scale and Meibomian gland dysfunction grading. The study was analyzed for correlation, using statistical tools of simple linear regression, Pearson correlation and Anova. Results: 328 pterygium patients were identified, and information collected. The average horizontal and vertical size of pterygium was 2.74 mm and 2.45 clock hours. The most common redness grading was intermediate (176/328:53.66%). The relationship between horizontal size, vertical size and redness of pterygium with dry eye symptoms and tear film was (R = 0.32, 0.29 and 0.64) with a significance of <0.001, 0.005 and <0.001. The strongest correlation found was in redness of pterygium with OSDI scores, TBUT and Oxford corneal staining scale (R = 0.58, -0.46 and 0.38) with a significance of <0.001. Conclusions: Pterygium patients were found to be 33.6 percent in this hospital based, retrospective cross-sectional study. Horizontal size, Vertical size and redness of pterygium were related to tear film and dry eye symptoms. Redness of pterygium was the most important clinical feature affecting tear film and dry eye symptoms.